A LITHOPEDION – AN UNUSUAL CALCIFIED ABDOMINAL PREGNANCY: A CASE REPORT - Ike Sulistiyowati; Siswidiyati; Setyawan, Agung; Arifah (Department of Radiology, Medical Faculty, University of Brawijaya, 2023)
Introduction: Lithopedion is an ectopic pregnancy that progresses to fetal mortality and calcification, as described in the introduction. It is uncommon, with a reported incidence of 1.5% to 2% of all ectopic pregnancies. The fetus expires and is not absorbed by the mother's body, but it evades maternal immunity by surrounding itself with a calcified shell. Lithopedion can be diagnosed through abdominal X-rays, ultrasonography, and CT imaging. Case presentation: A 73-year-old female complaining of abdominal mass for over three decades and radiating pain to the right hip for a month. The patient is multipara with a history of habitual abortion. There was an immobile abdominopelvic mass in palpation. The ultrasound showed a large calcified mass in the pelvic cavity. Abdominal and pelvic CT revealed a mummified fetus, depicting great detail of the fetal anatomy surrounded by a calcified membrane. The uterus was normal. Our case is suitable with lithokelyphopedion. Conclusion: Lithopedion is a seroius condition associated with high maternal and perinatal mortality rates. The condition was not identified during prenatal visits. A thorough history and physical examination are as important as imaging investigations in this setting. Keywords: lithopedion, lithokelyphopedion, calcified abdominal mass